Model Integrasi Pembelajaran Sains pada Kurikulum Pesantren di Pondok Pesantren Modern Alkautsar Simalungun - Febby Adinda; Siti Halimah; Yusnaili Budianti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the development of a curriculum that integrates science education into the pesantren curriculum at Alkautsar Modern Islamic Boarding School, Simalungun. It further examines the model of science learning integration implemented within the pesantren curriculum, the process of implementing integrative science learning, and the evaluation techniques employed at Alkautsar Modern Islamic Boarding School, Simalungun. This study imployed a qualitative research method with an analytical approach. Data were collected through in-depth interviews with the principal, vice principal for curriculum affairs, and subject teachers as the primary informants. In addition, field observations and document analysis were conducted to support the findings. Data were analyzed using the stages of data collection, data reduction, data display, and conclusion drawing. The findings reveal that: 1) In the curriculum development stage, Alkautsar Modern Islamic Boarding School, Simalungun, develops an integrative curriculum by using the school's vision, mission, and the Five Core Values (Panca Jiwa) of the pesantren as the primary foundation for educational implementation. The Merdeka Curriculum and the Kulliyatul Mu'allimin Al-Islamiyah (KMI) Curriculum are integrated contextually so that they complement each other while preserving their respective identities. 2) The science integration model implemented at the school consists of two main approaches: the interconnection model and the integrative model. The interconnection model is realized by aligning themes between science subjects and Islamic studies, while the integrative model is implemented by directly incorporating scientific concepts with Islamic values within the same learning process. 3) The implementation of integrative science learning is carried out consistently through the synergy between academic activities and the daily life of the pesantren. Learning is conducted using a student-centered approach combined with Project-Based Learning (PBL), halaqah, sorogan, and bandongan methods, classroom discussions, laboratory practicums, and experiential learning. 4) In terms of evaluation, Alkautsar Modern Islamic Boarding School, Simalungun, applies a comprehensive, continuous, and holistic assessment system. Evaluation is not limited to measuring students' cognitive achievement through written examinations, oral examinations, and laboratory practicums, but also assesses the development of attitudes, character, spirituality, the ability to apply knowledge in everyday life, and teachers' effectiveness in implementing integrative learning.